Prinsip Prinsip dan Kaidah Hukum Islam: Tidak Picik, Tidak Memberatkan, Diterapkan Secara Bertahap, Memperhatikan Kemaslahatan Manusia dan Mewujudkan Keadilan: Penelitian - Nazmi Septrina; Salma Salma; Muchlis Bahar (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The principles and rules of Islamic law are essentially established to realize human welfare, maintain justice, and uphold universal humanitarian values. Islamic law is not narrow-minded and rigid, but rather flexible, adaptive, and considers the social conditions of society. The principle of "la haraj" (not burdensome) demonstrates that Islamic law exists to provide convenience, not hardship, as emphasized in the maxim "al-masyaqqah tajlib al-taysir" (difficulty brings ease). The implementation of Islamic law is also carried out in stages (tadarruj), enabling society to adapt and fully internalize its values without causing social unrest. Thus, Islamic law emphasizes a balance between the text of sharia and the needs of human life, as well as between legal certainty and the common good. All of these principles lead to achieving the primary objectives of sharia (maqasid al-shari'ah), namely, safeguarding religion, life, intellect, lineage, and property, while upholding justice as the foundation of social life.